2008
DOI: 10.1007/s10530-008-9260-z
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific differences in chemosensory responses of freshwater turtles: consequences for competition between native and invasive species

Abstract: The red-eared slider (Trachemys scripta elegans) is an introduced invasive species in many Mediterranean countries that is displacing the populations of native endangered Spanish terrapins (Mauremys leprosa). However, it is relatively unknown how potential competitive interactions could be taking place. In many freshwater turtles, semiochemicals from different glands might facilitate species and sex recognition. We hypothesized that chemosensory detection of competitor species might affect space use and habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…They suggested remote identification and active avoidance of interactions with heterospecific competitors by the native species. Also, avoidance by M. leprosa of water with chemical cues of T. scripta has been experimentally demonstrated (Polo-Cavia et al 2009a), which suggests that Spanish terrapins actively avoid areas occupied by introduced sliders.…”
Section: Air -Water Temperature (°C)mentioning
confidence: 95%
See 1 more Smart Citation
“…They suggested remote identification and active avoidance of interactions with heterospecific competitors by the native species. Also, avoidance by M. leprosa of water with chemical cues of T. scripta has been experimentally demonstrated (Polo-Cavia et al 2009a), which suggests that Spanish terrapins actively avoid areas occupied by introduced sliders.…”
Section: Air -Water Temperature (°C)mentioning
confidence: 95%
“…Although the nature of the interaction between sliders and Spanish terrapins is not clear, it is possible that direct competition for food, refuges or basking places is present (Crucitti et al 1990). Recent studies indicated that sliders have diverse advantages over Spanish terrapins (Polo-Cavia et al 2008, 2009a. Competition for basking sites has been described between sliders and the European pond turtle (Emys orbicularis) (Cadi and Joly 2003), and field observations suggest that competition is very likely to occur also between sliders and the Spanish terrapin, as both turtle species are commonly forced to share basking sites (Díaz-Paniagua et al 2002;Pleguezuelos 2002), such as emergent rocks or logs, which may be a restricted resource in the wild (Cadi and Joly 2003).…”
Section: Introductionmentioning
confidence: 99%
“…When shared resources become limited, red-eared slider turtles negatively impact the growth of native turtles, and are also expected to cause long-term population declines in native species that are already threatened, such as the red-bellied turtle (Pseudemys rubriventris) (Pearson et al 2013(Pearson et al , 2015. Even the presence of slider turtle chemical stimuli can lead to the avoidance of such localities by native turtle species (Polo-Cavia et al 2009). While the import of T. s. elegans to the European Union has been prohibited since 1997, new records continue to be reported as pet animals that were imported before 1997 or bred in captivity are discarded in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…In direct competition, native turtles seem to rely on water-borne chemical cues to discriminate between conspecifics and heterospecifics, thus avoiding potential costly interactions with exotic turtles, deserting resources or displacing to less preferred areas (POLO-CAVIA et al, 2009a). Thus, the higher aggressiveness and dominance of sliders in competition for food or basking sites may lead native terrapins to a detriment in their nutritional state and thermoregulatory behaviour (POLO-CAVIA et al, 2010a.…”
Section: Synthesis and Future Researchmentioning
confidence: 99%